PATIENT DATA PROTECTION IN THE DIGITAL ERA (CHALLENGES AND LEGAL SOLUTIONS) - Ferianasari, Ineke Winda (International Journal of Social Service and Research, 2024)
Artificial intelligence (AI) has emerged as a promising technology in the field of healthcare, enabling the development of innovative solutions that enhance the quality and efficiency of medical services. The application of AI in the management of patient data has facilitated the acceleration, optimization, and precision of this process, which can subsequently improve the quality of healthcare services. This study aims to analyse the legal challenges that arise with the use of digital technology and artificial intelligence in patient data management, and to identify relevant legal solutions to overcome these problems. The study employs library research techniques, analysing statutory provisions and drawing on both written and unwritten positive law to examine legal issues. The results show that the integration of AI and digital technology in healthcare has yielded significant advantages, including enhanced efficiency, precision in diagnosis, and the harnessing of big data for patient care. However, a number of significant challenges remain, particularly with regard to the safeguarding of personal data. The formulation of an ethical framework for the utilisation of AI, the establishment of rigorous safety standards and the continuation of research in this domain are vital to enhance the advantages and mitigate the risks associated with the deployment of AI. It is imperative that health institutions and AI developers implement robust cybersecurity standards and periodic assessments for potential system vulnerabilities.